Annual Cycle of Turbulent Dissipation Estimated from Seagliders. Issue 19 (10th October 2018) - Evans, Dafydd Gwyn; Lucas, Natasha Sarah; Hemsley, Victoria; Frajka‐Williams, Eleanor; Naveira Garabato, Alberto C.; Martin, Adrian; Painter, Stuart C.; Inall, Mark E.; Palmer, Matthew R.
Abstract: The rate of dissipation of turbulent kinetic energy is estimated using Seaglider observations of vertical water velocity in the midlatitude North Atlantic. This estimate is based on the large‐eddy method, allowing the use of measurements of turbulent energy at large scales O (1–10 m) to diagnose the rate of energy dissipated through viscous processes at scales O (1 mm). The Seaglider data considered here were obtained in a region of high stratification (1 × 10 −4 < N < 1×10 −2 s −1 ), where previous implementations of this method fail. The large‐eddy method is generalized to high‐stratification by high‐pass filtering vertical velocity with a cutoff dependent on the local buoyancy frequency, producing a year‐long time series of dissipation rate spanning the uppermost 1, 000 m with subdaily resolution. This is compared to the dissipation rate estimated from a moored 600 kHz acoustic Doppler current profiler. The variability of the Seaglider‐based dissipation correlates with one‐dimensional scalings of wind‐ and buoyancy‐driven mixed‐layer turbulence. Plain Language Summary: Measuring ocean turbulence is crucial for understanding how heat and carbon dioxide are transferred from the atmosphere to the deep ocean. However, measurements of ocean turbulence are sparse. Here autonomous Seagliders are used to estimate turbulence in the surface kilometer of the North Atlantic Ocean. Using an estimate of the vertical water velocity from the flight of the Seaglider through the water, we estimate turbulence by assuming the energy of the largest turbulent fluctuations is representative of the energy dissipated at molecular scales. This approach has been used previously in an ocean region where the vertical gradient of density is small. Our results show that this previous approach fails when the vertical density gradient increases, as it does not account for other processes that are unrelated to turbulence. We introduce a generalized method that isolates only the turbulent processes by accounting for the strength of the vertical density gradient. We show that this new estimate agrees with other turbulence measurements. Our estimate also agrees well with a simple estimates of turbulence from atmospheric processes. This study therefore presents method that can be applied to existing and new Seaglider data to greatly increase our measurements of ocean turbulence. Key Points: Generalized method of estimating dissipation rate from Seagliders filtered by stratification increases scope of ocean turbulence estimates Annual cycle of turbulent dissipation in the top 1, 000 m in the North Atlantic reveals seasonal cycle of mixing One‐dimensional scaling for wind‐ and buoyancy‐derived turbulence explains annual cycle of dissipation